Low‐temperature investigation of natural iron‐rich oxoborates vonsenite and hulsite: thermal deformations of crystal structure, strong negative thermal expansion and cascades of magnetic transitions. Issue 6 (29th November 2021) - Biryukov, Yaroslav P.; Zinnatullin, Almaz L.; Cherosov, Mikhail A.; Shablinskii, Andrey P.; Yusupov, Roman V.; Bubnova, Rimma S.; Vagizov, Farit G.; Filatov, Stanislav K.; Avdontceva, M. S.; Pekov, Igor V.
Abstract : Vonsenite and hulsite were investigated by a set of in situ low‐temperature methods. Cascades of magnetic transitions were revealed in both oxoborates and the critical temperatures were determined. Anomalies in the unit‐cell parameters and thermal expansion of the oxoborates at critical temperatures were observed. Abstract : This work is devoted to an investigation of the magnetic properties and thermal behaviour of the natural oxoborates vonsenite and hulsite in the temperature range 5–500 K. The local environment, the oxidation states of the Fe and Sn atoms, and the charge distribution were determined using Mössbauer spectroscopy and are in accordance with a refinement of the crystal structure of hulsite from single‐crystal X‐ray diffraction data (SCXRD) in anisotropic approximation for the first time. The magnetic properties were studied by vibrating sample magnetometry (VSM) (5 ≤ T ≤ 400 K) and are reported for the first time for iron‐rich hulsite. Both oxoborates show a very complex magnetic behaviour. Cascades of magnetic transitions are revealed and the critical temperatures were determined. The sequences of magnetic transitions in both vonsenite and hulsite with increasing temperature were found to be as follows: magnetically ordered state → partial magnetic ordering → paramagnetic state. According to X‐ray diffraction data (93 ≤ T ≤ 500 K), these processes are accompanied by anomalies in the unit‐cell parameters and thermal expansion of the oxoborates at critical temperatures. A strong negative volume thermal expansion is observed for both oxoborates at temperatures below ∼120 K.